House construction of time scheduling using criticalpath method (CPM) in selili district - Surahman, Surahman; Saputri, Yuni; F. Athoya, Muhammad; H. Rabbani, Ihwan; Rahmayanti, Nor I.; Hidayati, Dwi (Enrichment : Journal of Management, 2024)
Project time management is the process of planning, compiling, and monitoring the project activity schedule. This is an approach to meeting needs in construction projects that involves managing the planning, design and project implementation processes in an integrated manner. The aim of this research is to determine the effect of accelerating work duration using the CPM (Critical Path Method) method on the Selili sub-district project. The acceleration alternative used is by cutting work time and combining several jobs that can be done at one time by looking for advanced calculations and backward and critical path calculations use the critical path which is then accelerated in the form of shortening the time of activities on the critical path. Then a float diagram is created to determine the work that has been cut. The results obtained from the work using the CPM method are a summary of work days of 15 days from the initial plan which was planned to be completed within 163 days, after going through the critical path using the critical path and knowing the results of the forward and backward calculations then depicted in a float diagram that the work can be completed within 148 days